Developing an English language textbook evaluation checklist: a focus group study - Mukundan, Jayakaran; Hossein, Vahid Nimehchisalem; Hajimohammadi, Reza (Center for Promoting Ideas, 2011)
English Language Teaching (ELT) textbook evaluation checklists are instruments that help teachers the most appropriate books for their learners. This paper presents a phase of an on-going project proposed out of the need for a valid, reliable and a practical checklist. The phase includes a focus group study designed to further refine a checklist previously developed by the present researchers (Mukundan, Hajimohammadi, & Nimehchisalem, 2011). More specifically, the participants in the focus group (n=6) helped the developers improve the items of the checklist in reference to their clarity and inclusiveness. The study commenced in the form of an unstructured interview in which the participants brainstormed on the evaluative criteria that should be considered in evaluating ELT textbooks. This was followed by a structured interview in which the participants were provided with a copy of the checklist. They were free to reword, delete or add items that they considered necessary. As a result of this study, 14 items were added to the checklist while two were reworded. The findings are expected to be useful for English language teachers, ELT material developers and evaluators as well as curriculum developers. Further study is required to improve the instrument.